KEEFEKTIFAN MEDIA POWTOON TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA KELAS IV SD NEGERI 2 NALUMSARI KABUPATEN JEPARA - Syaifatul Anisa Fitriana; Muhammad Arief Budiman; Suyitno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The background that drives this research is that teachers have not used learning media, have not applied appropriate learning models and methods in learning English. lack of teacher interaction in learning so that students become passive. This type of research is quantitative research in the form of pre-experimental designs with the form of One-Shot Case Study. The study population was all fourth grade students at SDN Nalumsari, Jepara Regency, in the 2022/2023 academic year. The samples taken were all 4th grade students as many as students. Based on the results of research that has been carried out at SD Negeri 2 Nalumsari, Jepara Regency regarding the effectiveness of powtoon media on English learning outcomes for fourth grade students of SD Negeri 2 Nalumsari, Jepara Regency, the following results were obtained. The results of posttest data recapitulation of the results of learning English for fourth grade students of SD Negeri 2 Nalumsari, Jepara Regency using the Powtoon learning media, the mean or average value is 82.5, for the highest score obtained is 95, while for the lowest score is 70. Furthermore, the percentage There are 25 students who complete the study with a percentage of 89.3% (25 students) and 3 students who have not finished with a percentage of 10.7% (3 students) and the percentage of classical learning completeness is more than 75%, which is 89.3%. For the results of the normality test, the value of Sig (2 tailed) is 0.200 > 0.05 and the hypothesis test is that the average value of English learning outcomes given learning using Powtoon media is greater than the KKM value or 82.5 > 75. From the results It can be concluded that the use of powtoon media is effective on learning outcomes of English subjects in fourth grade students at SD Negeri 2 Nalumsari, Jepara Regency.